2005
DOI: 10.1152/ajpheart.00068.2005
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II AT1 receptors regulate ACE2 and angiotensin-(1–7) expression in the aorta of spontaneously hypertensive rats

Abstract: When increased in vascular tissues, angiotensin-converting enzyme 2 (ACE2), a carboxypeptidase that hydrolyzes angiotensin II to angiotensin-(1-7), may augment the growth inhibitory and vasodilatory effects of the heptapeptide. We investigated the regulation of ACE2 and angiotensin-(1-7) expression in aortas and carotid arteries of 12-wk-old male spontaneously hypertensive rats (SHR) by determining the effect of sustained angiotensin type 1 (AT 1) receptor blockade with olmesartan (10 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 , n ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
167
3
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 34 publications
8
167
3
7
Order By: Relevance
“…In this study, we showed increased ACE2 gene expression in the aorta but not the carotid arteries of SHRs given olmesartan for 2 weeks. 50 Additional evidence for a transcriptional regulation of the ACE2 enzyme is found in the data obtained by Gallagher et al 51 in neonatal rat cerebellar or medullary astrocytes. In these studies, we showed that Ang II-mediated reduction in ACE2 mRNA was blocked by losartan or valsartan, whereas PD123319 was ineffective.…”
Section: Ace2 and Ang-(1-7)mentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, we showed increased ACE2 gene expression in the aorta but not the carotid arteries of SHRs given olmesartan for 2 weeks. 50 Additional evidence for a transcriptional regulation of the ACE2 enzyme is found in the data obtained by Gallagher et al 51 in neonatal rat cerebellar or medullary astrocytes. In these studies, we showed that Ang II-mediated reduction in ACE2 mRNA was blocked by losartan or valsartan, whereas PD123319 was ineffective.…”
Section: Ace2 and Ang-(1-7)mentioning
confidence: 83%
“…Treatment with Ang-(1-7) resulted in both a dose-and time-dependent reduction in serum-stimulated DNA synthesis in all 3 of the cell lines, with an IC 50 in the subnanomolar range. The Ang-(1-7) receptor antagonist D-Ala 7 -Ang-(1-7) blocked the attenuation of the serumstimulated DNA synthesis of SK-LU-1 cells by Ang-(1-7), whereas neither AT 1 nor AT 2 angiotensin receptor subtype antagonists prevented the response to the heptapeptide.…”
Section: An Additional Perspectivementioning
confidence: 95%
“…The interaction between ACE and ACE2 is demonstrated by the observation that ACE inhibition results in elevation of Ang 1-7 in vivo and blockade of Ang 1-7 with a specific antagonist reverses the antihypertensive effects of lisinopril. 4,6,18 Furthermore, a recent study demonstrated that lentiviral delivery of ACE2 can reverse cardiac hypertrophy in rats, suggesting not only that ACE2 is beneficial, but that manipulation of ACE2 may have therapeutic potential. 19 Direct evidence for ACE2 in the development of hypertensive cardiopathy and kidney disease comes from the ACE2 gene knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the hypothesis of there being another isoform of ACE present in the aorta which is inhibited by Lisinopril as well but does not cleave Hippuryl-His-Leu nor does it crossreact with our immunohistochemistry antibody. The local vascular RAS activity in aortic tissue has been demonstrated in rat by Igase et al (2005) and distinguished from that in other vascular beds, namely, carotid arteries. Also, as noted above, in homogenates, in contrast to functional measurement in the aortic rings, the normal vascular (ACEi) on the contractile response to AngI was studied; it showed a shift toward the right in the curves, with subsequently no differences between the conversion from AngI to AngII anymore (d) architecture is destroyed.…”
Section: Described This Polymorphism In Inbred Brownmentioning
confidence: 99%